How Does It Feel to Be Part of the Minority? Impacts of Perspective-Taking on Prosocial Behaviors - Marisol Rodríguez Chatruc; Sandra V. Rozo (Institute of Labor Economics (IZA), 2021)
Can online experiences that illustrate the perspective of the everyday life of a minority group improve behaviors of the dominant towards the minority group? We explore the case of natives and refugees by randomly assigning 850 natives to: i) an online game that immerses natives in the life decisions of refugees and ii) a real-life documentary about the migration process of refugees. Both treatments effectively improve altruism and reduce prejudice from natives towards migrants. The impacts of both treatments are not statistically different in any of the other outcomes that we examine.
Keywords: D72; F2; O15; R23; 330; migration; redistribution; trust